Sociology of sociology: Strengthening the role of social sciences as a new priority of climate and sustainability policy - Andrzej Strzałkowski (Economic and Environmental Studies (E&ES), 2016)
Today, there are a lot of studies on climate change and sustainability from social sciences' perspectives. Achievements of sociology, psychology or political sciences can be extremely helpful in designing, adopting, implementing and evaluating of effective climate and sustainability policy. However, so far, social sciences, excluded neoclassical economics and dogmatic law, have being marginalizing in the mainstream of climate and sustainability science, politics and discourse. Social studies also have not been included in the IPCC' and other important agencies' reports. In consequence, there is a significant gap in our understanding many facets of climate change and other civilizational threats and possible tools to mitigating them, which may be a reason of the pure effectiveness of the past policies. In this paper I would like to present a few of examples, what social sciences, especially sociology and psychology can contribute to climate and sustainability discourse, as well as, propose hypothesis which could explain marginalization of social sciences today. I will conclude that there are needed more studies about reasons of little widespread social perspective and barriers of incorporating social sciences' approaches to political and non-governmental sphere. In my opinion, in these studies could be used perspectives of cognitive and social psychology or constructivist version of sociology of knowledge, then sociology could became object of its own research, which will result in such kind of 'sociology of sociology'.
Keywords: A14; Q01; D01; D03; A11; A13; A12; D12; D22; O44; 330; Social sciences; sustainable development; climate change; global warming; sociology of knowledge; sustainability science; climate policy; sustainability policy; sociology of climate change; psychology of sustainability